Comparison of a new-generation fecal immunochemical test (FIT) with guaiac fecal occult blood test (gFOBT) in detecting colorectal neoplasia among colonoscopy-referral patients - Guimarães, Denise Peixoto; Fregnani, Jose Humberto; Reis, R. M.; Taveira, Leonardo Nogueira; Scapulatempo-Neto, Cristovam; Matsushita, Marcus; Silva, Sandra Regina Morini; Oliveira, Ceyton Zanardo; Longatto, Adhemar; Eklund, Carita; Paloheimo, Lea; Mauad, Edmundo; et al. (Anticancer research, 2019)
The aim of the present study was to compare fecal immunochemical tests (FITs) for colorectal cancer (CRC) screening with the traditional guaiac-based FOB tests (gFOBT). Background/Aim: The aim of the present study was to compare fecal immunochemical tests (FITs) for colorectal cancer (CRC) screening with the traditional guaiac-based FOB tests (gFOBT). Materials and Methods: A cohort of 368 colonoscopy-referral patients were evaluated by i) the new-generation FIT: ColonView quick test (CV; Biohit Oyj, Finland) and ii) a conventional gFOBT HemoccultSENSA (HS; Beckman Coulter, USA). Three fecal samples were requested for both assays, and all subjects underwent diagnostic colonoscopy with biopsy confirmation. Sensitivity (SE), specificity (SP), positive predictive value (PPV), negative predictive value (NPV) and area under curve (AUC) were calculated for both tests using three endpoints: adenoma (A), advanced adenoma (AA) and adenocarcinoma (AC). Results: Colonoscopy and biopsies disclosed normal mucosa in 90/378 (24.5%) subjects, early A in 108/368 (29.3%) cases, AA in 48/368 (13.0%) and AC in 37/368 (10.1%), and non-neoplastic conditions in the remaining 85 (30.3%). For the AC endpoint, the CV (Hb/Hp) test had 94.6% SE and 65.1% SP (AUC=0.799), while the HS test had SE of 75.7% and SP of 84.3% (AUC=0.800). For the A endpoint, the difference between CV and HS was even more pronounced; SE of 44.2% and 19.2%, respectively (p<0.0001). Hb and Hb/Hp complex of the CV test showed equal performance for all endpoints. Conclusion: Sensitivity (94.6%) of the ColonView quick test for the most reproducible endpoint (invasive CRC) far exceeded the pooled sensitivity (79%) estimated in a recent meta-analysis for 8 common FIT brands. As shown in a previous study, ColonView quick test is superior in SE to HemoccultSENSA test, making CV a perfect FIT for organized CRC screening The Authors thank Ms. Gabriela de Oliveira for the identification and tracking all the patients included in the study. The Authors would also like to give special thanks to Ms. Thais Thalarico for assisting in data analysis, as well as to Ms. Maraisa Costa and Ms. Adriana Carloni for running the analysis of the gFOBT and FIT tests. This study was supported by Biohit Oyj.